The Digital Revolution - United Nations Women; Judy Wajcman; Erin Young; Anna Fitzmaurice (United Nations, 2020)
The digital revolution brings immense potential to improve social and economic outcomes for women. Yet, it also poses the risk of perpetuating existing patterns of gender inequality. This report begins by outlining a conceptual framework for understanding the mutual shaping relationship between gender and technology. It then focuses on three areas to identify opportunities and risks in the digital revolution: education, work, and social/welfare services.